Regional Economic Outlook, October 2014 : Staying the Course. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2014)
Growth in much of Sub-Saharan Africa is expected to remain strong, driven by efforts to invest in infrastructure and strong agricultural production. The current Ebola outbreak in Guinea, Liberia, and Sierra Leone is exacting a heavy toll, with spillovers to neighboring countries. External threats to the region's overall positive outlook include global financial conditions and a slowdown in emerging market growth.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet